Financial Support for Small and Medium-Sized Enterprises in China Amid COVID-19 - M. Jiang (Финансы: теория и практика, 2020)
Small and medium-sized enterprises (SMEs) are vital drivers of China’s economy. As in any other country, SMEs in Chinaare exceptionally exposed to the devastating effects of the COVID-19 outbreak. The aim of the paper is to assess the impact of the pandemic on SMEs in China and study the effectiveness of the government’s support for SMEs through the crisis. The methodologies applied by the authors included the historical and logical method, the method of the rising from the abstract to the concrete, synthesis, comparative factor analysis, grouping and graphical methods, as well as a systematic and statistical approach. The authors investigate the main policies and initiatives launched in support of smaller businesses and implemented by the People’s Bank of China, the Ministry of Finance, the National Development and Reform Commission, the Ministry of Industry and Information Technology, as well as by the two national regulatory authorities –– China Banking and Insurance Regulatory Commission and China Securities Regulatory Commission. In this paper the authors analyze the direct and indirect support available to SMEs through financial institutions. The study leads to the conclusions that the state support for SMEs has been effective and helped to avoid a sharp decline in production. However, the spread of the disease in other countries may threaten the recovery of the Chinese economy.